Brazilian journal of transplantation - Associação Brasileira de Transplante de Órgãos (Associação Brasileira de Transplante de Órgãos, 2021)
Concerned with all activities related to organ and tissue transplantation, especially in Brazil and Latin America.
Keywords: Transplantation of organs, tissues, etc : Periodicals; Transplantation of organs, tissues, etc : Brazil : Periodicals; Transplantation of organs, tissues, etc : Latin America : Periodicals; Transplantation of organs, tissues, etc; Brazil; Latin America